2024
DOI: 10.3389/fpsyt.2024.1352824
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adverse childhood experiences on mental health, sexual risk behaviors, and alcohol consumption in adulthood

Miguel Landa-Blanco,
Gabriela Vásquez,
Gretel Portillo
et al.

Abstract: The purpose of the study was to determine how Adverse Childhood Experiences (ACE) relate to adulthood flourishing, symptoms of depression, anxiety, somatization, self-reported health, sexual risk behaviors, and alcohol consumption. A quantitative cross-sectional methodology was used. A total of 452 adults completed the survey. The most prevalent ACE include physical abuse (44.69%), separation/divorce of parents (41.81%), living with someone with alcohol problems (39.38%), and being sworn, insulted, or humiliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Recent studies from Honduras have also reported that certain ACEs exhibit notably detrimental effects on mental health outcomes. These include instances of coerced sexual activity, exposure to domestic violence within the family, verbal degradation, and residing with individuals grappling with mental health challenges, substance abuse problems, or incarceration histories ( Landa-Blanco et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies from Honduras have also reported that certain ACEs exhibit notably detrimental effects on mental health outcomes. These include instances of coerced sexual activity, exposure to domestic violence within the family, verbal degradation, and residing with individuals grappling with mental health challenges, substance abuse problems, or incarceration histories ( Landa-Blanco et al, 2024 ).…”
Section: Introductionmentioning
confidence: 99%